Resolving generic limits in Cyperaceae tribe Abildgaardieae using targeted sequencing. (4th January 2021) - Larridon, Isabel; Zuntini, Alexandre R; Barrett, Russell L; Wilson, Karen L; Bruhl, Jeremy J; Goetghebeur, Paul; Baker, William J; Brewer, Grace E; Epitawalage, Niroshini; Fairlie, Isabel; Forest, Félix; Sabino Kikuchi, Izai A B; et al.
Abstract: Morphological characterizations of genera in Cyperaceae tribe Abildgaardieae have been highly problematic and the subject of much debate. Earlier molecular phylogenetic studies based on Sanger sequencing and a limited sampling have indicated that several generic circumscriptions are not monophyletic. Here, we provide the first phylogenetic hypothesis for Abildgaardieae using targeted sequencing data obtained with the Angiosperms353 enrichment panel for 50 species. We test whether recent taxonomic decisions made based on Sanger sequencing data are validated by our targeted sequencing data. Our results support subsuming the small African genus Nemum into the large genus Bulbostylis and subsuming the monotypic genus Crosslandia into the diverse genus Fimbristylis . Also, our results support the recent publication of the new genus Zulustylis for two African species previously placed in Fimbristylis . Furthermore, we investigate the phylogenetic placement of recently described tropical Australian endemic species of Actinoschoenus, which are recognized here as the new morphologically cryptic genus Scleroschoenus . Based on our phylogenetic hypothesis and supported by morphological data, we recognize the genus Abildgaardia . The placement in Abildgaardieae of two monotypic genera Nelmesia and Trichoschoenus, only known from the type collections from the Democratic Republic of Congo and Madagascar, respectively, are also discussed. New combinations and lectotypifications are made in Abildgaardia, Actinoschoenus, Arthrostylis and Scleroschoenus .